PENGARUH MODEL JIGSAW MELALUI MEDIA PUZZLE PADA PELAJARAN MATEMATIKA DENGAN MATERI PECAHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD 067257 MEDAN AMPLAS - Landong, Ahmad; Sobirin, Ahmat; Husna, Asmaul; Apridayanti, Lisa; Nabila, Nabila; Sinta, Sinta; Nabila, Talitha; Rosadi, Ray Ade; Amalia, Ridani; Ardina, Zifanna; Ardini, Zifanny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Jigsaw type cooperative learning model combined with puzzle media on the mathematics learning outcomes of fourth grade students of SD 067257 Medan Amplas on fraction material. The background of this study is based on students' low understanding of the concept of fractions except for the presentation of abstract material and the use of conventional methods that are less interactive. The research method used is research and development (Research and Development) with the ADDIE model, and the Realistic Mathematics Education (RME) approach to deliver material with real contexts. The subjects of the study were 20 fourth grade students. The results showed that there was a significant increase in student learning outcomes in the experimental class (average posttest 83.7) compared to the control class (average posttest 72.1). The t-test showed a significance value of 0.002 <0.05, which indicated a significant difference in learning outcomes between the two groups. These findings announce that the integration of the Jigsaw model with puzzle media is able to create a more active, collaborative, and enjoyable learning atmosphere, as well as significantly improve students' understanding of fraction material. This study provides theoretical and practical contributions to the innovation of mathematics learning strategies at the elementary school level.